2023
DOI: 10.1038/s41398-023-02401-w
|View full text |Cite
|
Sign up to set email alerts
|

Parsing brain-behavior heterogeneity in very preterm born children using integrated similarity networks

Abstract: Very preterm birth (VPT; ≤32 weeks’ gestation) is associated with altered brain development and cognitive and behavioral difficulties across the lifespan. However, heterogeneity in outcomes among individuals born VPT makes it challenging to identify those most vulnerable to neurodevelopmental sequelae. Here, we aimed to stratify VPT children into distinct behavioral subgroups and explore between-subgroup differences in neonatal brain structure and function. 198 VPT children (98 females) previously enrolled in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 115 publications
(145 reference statements)
1
4
2
Order By: Relevance
“…Our post-hoc analyses aimed to explore whether specific enriching factors, or lack of certain social or clinical risk factors, protected the VPT adults belonging to the Resilient subgroup from developing an At-risk behavioural profile. In contrast to previous studies in VPT children, we found that perinatal clinical risk was not higher in VPT adults who belonged to an At-risk (vs Resilient) subgroup (Hadaya et al, 2023; Poehlmann et al, 2015). Social risk, on the other hand, may be specifically related to the difficulties observed in the VPT At-risk subgroup, which contained more VPT adults from more socially disadvantaged backgrounds compared to the Resilient subgroup, while this relationship was not observed in FT adults.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our post-hoc analyses aimed to explore whether specific enriching factors, or lack of certain social or clinical risk factors, protected the VPT adults belonging to the Resilient subgroup from developing an At-risk behavioural profile. In contrast to previous studies in VPT children, we found that perinatal clinical risk was not higher in VPT adults who belonged to an At-risk (vs Resilient) subgroup (Hadaya et al, 2023; Poehlmann et al, 2015). Social risk, on the other hand, may be specifically related to the difficulties observed in the VPT At-risk subgroup, which contained more VPT adults from more socially disadvantaged backgrounds compared to the Resilient subgroup, while this relationship was not observed in FT adults.…”
Section: Discussioncontrasting
confidence: 99%
“…Our post-hoc analyses aimed to explore whether specific enriching factors, or lack of certain social or clinical risk factors, protected the VPT adults belonging to the Resilient subgroup from developing an At-risk behavioural profile. In contrast to previous studies in VPT children, we found that perinatal clinical risk was not higher in VPT adults who belonged to an At-risk (vs Resilient) subgroup (Hadaya et al, 2023;Poehlmann et al, 2015).…”
Section: Differences In Rsfc and Behavioural Outcomes Between Vpt And...contrasting
confidence: 99%
See 3 more Smart Citations